Determinação espectrofotométrica de hexametilenotetramina (HMT) em medicamentos, utilizando ácido cromotrópico e forno de micro-ondas - Fagnani, Enelton; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Sociedade Brasileira de Química, 2009)
This paper proposes a methodology for spectrophotometric determination of hexamethylenetetramine (HMT) by using chromotropic acid in a phosphoric acid media employing a domestic microwave oven as a source of heating. The reddish-purple soluble product is quantitatively formed after 30 s of irradiation and obeys the Beer´s law in the range between 0.1-1.2 mg L-1 HMT (r = 0.99925). The method was applied successfully in commercial pharmaceutical preparations containing dyes in their composition. The results showed that the method proposed is feasible for simplicity, speed, low cost, precision and accuracy when compared with United States Pharmacopeia official method.
Spectrophotometric determination of hexamethylenetetramine (HMT) in pharmaceutical preparations using chromotropic acid and microwave oven
Keywords: hexamethylenetetramine; chromotropic acid; microwave oven